MONITORING OF WATER QUALITY AND TRIHALOMETHANES CONCENTRATIONS IN SOME DRINKING WATER PLANTS (British Journal of Global Ecology and Sustainable Development, 2022)
Chlorination is commonly used to inactivate or control microbial populations in the treated water, Disinfection by products are formed like trihalomethanes (THMs) when the chlorine react with organic matter in the water, This studies conducted annually to estimation the THMs and monitoring of water quality in river water during 2019-2020 for eight months. Water samples were collected from water purification plant (Al-Hashimiyah union project ), The total concentration of THMs ranged between (11.6 – 42.2 μg/l) in the water purification plants. THM levels increased during the summer when recorded highest values on July and August with a comparison to the lowest values ding winter months (December and January). as well as results physical and chemical tests for the station during the study period. Air and water temperature was ranged of (12-49 C°), and (13-32 ° C), Turbidity (3- 83.6 NTU), PH (7.4 – 9.8), Total Dissolved Solids (540-1121 mg / L), E.C (813-1299 μ g / cm) and TSS (2-42 mg / L) TH (CaCO3) (160-390)mg / l dissolved oxygen It is (5-14) mg /l , free residual chloride (ND – 4.0 mg / l) , total al-kalinity (140-260) mg / l, phosphate (PO4) (0.1 – 0.5) mg /l, bromide (Br) ( 0.5 -0.1 mg /l ).